Experience Informed Philosophy - Tegan W Nusser (Educational Considerations, 2020)
John Dewey's philosophy of education did not arise in a vacuum. Much as Dewey himself would have recognized, his experiences shaped his philosophy. The experiences described include Dewey's time as a boy in Burlington, Vermont; his graduate education at Johns Hopkins University, and his first academic post at the University of Michigan; concluding with his time at the University of Chicago with his famous laboratory school. Following each narrative, Dewey's experiences are connected with and compared to his landmark publication Democracy and Education. Special consideration to the alignment of theory and practice helps to guide interpretation of his experiences with his emerging philosophy. Local and regional contexts are provided to consider the situated context of each of the geographically organized narratives. Included is a discussion of the philosophical contributions of Kant, Vermont Transcendentalism, and Hegelianism to Dewey's philosophy. Additionally included are the contributions of Alice Chipman Dewey, Jane Addams, and Ella Flagg Young to Dewey's thinking.
Keywords: Dewey; Philosophy; History; Education; Intersectionality